Prey specialization and morphological conformation of wolves associated with woodland caribou and moose - Wiwchar, David M.A.; Mallory, Frank F. (Rangifer, 2012)
Morphological analysis of wolves associated with woodland caribou in late succession boreal coniferous forests north of the commercial cut line and those associated with moose in early succession boreal deciduous forests south of the commercial cut line were studied in Ontario. Socalled “moose-wolves” could readily be distinguished from “caribouwolves” in both genders using a few morphological measurements. Wolves associated with woodland caribou were significantly smaller in most measurements, and increased in size within seven years post-harvest as moose totally replaced caribou in the ecosystem. Whether this change in wolf morphology is related to micro-evolutionary change, the migration of larger “moose-wolves” into the area, or both, remains unclear.